A Rapid Review of Sexual Wellbeing Definitions and Measures: Should We Now Include Sexual Wellbeing Freedom?. Issue 7 (2nd September 2019) - Lorimer, Karen; DeAmicis, Leyla; Dalrymple, Jenny; Frankis, Jamie; Jackson, Louise; Lorgelly, Paula; McMillan, Lesley; Ross, Jonathan
Abstract : An increasing number of studies refer to sexual wellbeing and/or seek to measure it, and the term appears across various policy documents, including sexual health frameworks in the UK. We conducted a rapid review to determine how sexual wellbeing has been defined, qualitatively explored and quantitatively measured. Eligible studies selected for inclusion from OVID Medline, PsychInfo, PubMed, Embase, CINAHL were: in English language, published after 2007, were peer-reviewed full articles, focused on sexual wellbeing (or proxies for, e.g. satisfaction, function), and quantitatively or qualitatively assessed sexual wellbeing. We included studies with participants aged 16–65. Given study heterogeneity, our synthesis and findings are reported using a narrative approach. We identified 162 papers, of which 10 offered a definition of sexual wellbeing. Drawing upon a socio-ecological model, we categorised the 59 dimensions we identified from studies under three main domains: cognitive-affect (31 dimensions); inter-personal (22 dimensions); and socio-cultural (6 dimensions). Only 11 papers were categorised under the socio-cultural domain, commonly focusing on gender inequalities or stigma. We discuss the importance of conceptualising sexual wellbeing as individually experienced but socially and structurally influenced, including assessing sexual wellbeing freedom: a person's freedom to achieve sexual wellbeing, or their real opportunities and liberties.